Untangling Genomes of Novel Planctomycetal and Verrucomicrobial Species from Monterey Bay Kelp Forest Metagenomes by Refined Binning - Vollmers, John; Frentrup, Martinique; Rast, Patrick; Jogler, Christian; Kaster, Anne-Kristin (Frontiers in Microbiology, 2017)
The kelp forest of the Pacific temperate rocky marine coastline of Monterey Bay in California is a dominant habitat for large brown macro-algae in the order of Laminariales. It is probably one of the most species-rich, structurally complex and productive ecosystems in temperate waters and well-studied in terms of trophic ecology. However, still little is known about the microorganisms thriving in this habitat. A growing body of evidence suggests that bacteria associated with macro-algae represent a huge and largely untapped resource of natural products with chemical structures that have been optimized by evolution for biological and ecological purposes. Those microorganisms are most likely attracted by algae through secretion of specific carbohydrates and proteins that trigger them to attach to the algal surface and to form biofilms. The algae might then employ those bacteria as biofouling control, using their antimicrobial secondary metabolites to defeat other bacteria or eukaryotes. We here analyzed biofilm samples from the brown macro-algae Macrocystis pyrifera sampled in November 2014 in the kelp forest of Monterey Bay by a metagenomic shotgun and amplicon sequencing approach, focusing on Planctomycetes and Verrucomicrobia from the PVC superphylum. Although not very abundant, we were able to find novel planctomycetal and verrucomicrobial species by an innovative binning approach. All identified species harbor secondary metabolite related gene clusters, contributing to our hypothesis that through inter-species interaction, microorganisms might have a substantial effect on kelp forest wellbeing and/or disease-development.